Synsphyronus armasi, a new species (Pseudoscorpiones: Garypidae) from the Pilbara region of Western Australia - Harvey, Mark S. (Zootaxa, 2025)
A new species of the Australasian genus Synsphyronus Chamberlin, 1930, is described from north-western Australia. Like other species of the genus, Synsphyronus armasi sp. nov. has a reduced complement of trichobothria on the chelal fingers.